Ghoulfriends 'til the end - Daneshvari, Gitty (Little, Brown and Company, 2014)
It is bad times at Monster High because a secret organization of older monsters is determined to preserve their hierarchy, and it is up to the ghoulfriends...Rochelle, Rebecca, and Venus...to stop ASOME, protect their school, and rescue their friends
Keywords: High schools -- Juvenile fiction; Monsters -- Juvenile fiction; Secret societies -- Juvenile fiction; Friendship -- Juvenile fiction; High schools; Schools; Monsters; Secret societies; Friendship; Kinderbuch